Identifying students perceptions and improving supervisors support for completion of research dissertations - Perera, K.D.R.L.J.; Lekamge, G.D.; Karunanayaka, S.P.; Ariyaratne, A.; Kugamoorthy, S. (University of Jaffna, 2012)
The number of students enrolled in post graduate programmes in Universities worldwide has been improved substantially in the recent past with the increasing social demand for higher education and the incorporation of open and distance learning methods. Many graduate students are adult learners with diverse characteristics and backgrounds .As an essential component of the post graduate programmes, students are required to complete a research dissertation under a supervisor that could project discipline values such as conceptual innovation, methodological rigor, and substantive content. But a considerable amount of students do not complete their research dissertations due to various reasons. In this paper we propose some valuable actions to be taken to improve the completion rate of dissertations in Master of Education Degree Programme. It was revealed that the majority of students’ main expectations from participating in the intervention programme were to complete the research. In addition, their motivation has increased to complete the research due to the action research. Further, the presentations/discussions used during the workshops were very useful and they were satisfied with the intervention programme. The most needed support was related to frequent guidance, opportunity to contact by phone/email, immediate feedback, effective communication and friendly support. In addition to supervisors support there were personal, family and work place problems. It was suggested that there should be continuous workshop and guidance. Moreover, they needed immediate feedback for chapters. Further, they needed study leave, direction to individual supervisors and deadlines. It was suggested that this type of intervention programme should be started at the beginning of the programme. Most of the students proceeded to complete the research. And also almost all have appreciated the intervention programme. The action research was a very effective procedure to complete the research dissertations